VOPP1::EGFR fusion is associated with NFκB pathway activation in a glioneural tumor with histological features of ganglioglioma - Max Braune; Mathias Stiller; Cordula Scherlach; Florian Wilhelmy; Katja Jähne; Wolf C. Müller; Alonso Barrantes-Freer (Acta Neuropathologica Communications)
Abstract Glioneural tumors are primary brain tumors that consist of both neural and glial neoplastic cells, often presenting with seizures and primarily affecting children and young adults. Specifically, gangliogliomas are composed of neoplastic ganglion and glial cells, accompanied by other characteristic histological features such as lymphoid cuffing, eosinophilic granular bodies, and Rosenthal fibers. Oncogenic driver mutations and gene fusions have been shown to be of prognostic significance in gangliogliomas and can offer potential therapeutic targets. Typical molecular alterations are mitogen-activated protein kinase (MAPK) pathway activations with BRAF p.V600E being the most frequent one. Here, we report for the first time a gene fusion between epidermal growth factor receptor (EGFR) and vesicular, overexpressed in cancer, prosurvival protein 1 (VOPP1) as a potential oncogenic driver in a glioneuronal tumor morphologically resembling ganglioglioma. VOPP1::EGFR fusion associated with the activation of nuclear factor kappa-light-chain-enhancer of activated B cells (NFκB) signaling. Furthermore, we provide histological and epigenetic findings and clinical outcome. The case expands the known molecular spectrum of oncogenic drivers in glioneuronal tumors and provides a link to potentially prognostic and therapeutically relevant alterations.